The use of nondirected donor organs in living donor liver transplantation: Perspectives and guidance. Issue 6 (8th January 2022) - Fox, Alyson N.; Liapakis, AnnMarie; Batra, Ramesh; Bittermann, Therese; Emamaullee, Juliet; Emre, Sukru; Genyk, Yuri; Han, Hyosun; Jackson, Whitney; Pomfret, Elizabeth; Raza, Muhammad; Rodriguez‐Davalos, Manuel; et al.
Abstract: Interest in anonymous nondirected living organ donation is increasing in the United States and a small number of transplantation centers are accumulating an experience regarding nondirected donation in living donor liver transplantation. Herein, we review current transplant policy, discuss emerging data, draw parallels from nondirected kidney donation, and examine relevant considerations in nondirected living liver donation. We aim to provide a consensus guidance to ensure safe evaluation and selection of nondirected living liver donors and a schema for just allocation of nondirected grafts.